2022
DOI: 10.3389/fsufs.2022.832841
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Bio-Based Fertilizer Integration Into Conventional Grassland Fertilization Programmes on Soil Bacterial, Fungal, and Nematode Communities

Abstract: Phosphorus (P) is an essential plant macro-nutrient applied to soil in agriculture, mainly sourced from non-renewable mined phosphate-rock, of which readily accessible reserves are currently under pressure, while global food demand continues to grow. Meanwhile, an abundance of P is lost in waste-streams. Hence, bio-based fertilizers are increasingly produced using nutrient-recovery technologies and evaluated as a sustainable fertilizer alternative. However, there is little knowledge of how these products affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 86 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…This observation could be associated with changes in certain bacterial populations. In fact, studies on bacterial community response to STR found that actinobacterial populations were stimulated by STR from a wastewater treatment plant [48] and from municipal waste [98]. More specifically, Bastida et al (2019) [48] found that the application of STR increased the abundance of Streptomycetales.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be associated with changes in certain bacterial populations. In fact, studies on bacterial community response to STR found that actinobacterial populations were stimulated by STR from a wastewater treatment plant [48] and from municipal waste [98]. More specifically, Bastida et al (2019) [48] found that the application of STR increased the abundance of Streptomycetales.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies confirm that some BBR and/or their derivates contain biologically active substances (Fig. 3) which can induce significant implications to biota, particularly affecting fungi and bacteria 119 as well as higher plants. 120 Alterations in bacterial communities and their compositions are mainly due to shifts in soil physicochemical parameters, such as pH elevation, increased electrical conductivity, and enhanced levels of dissolved organic matter and/or nutrient availability 121–125 (Fig.…”
Section: Bio-based Resources (Bbr) and Implications To Biotamentioning
confidence: 96%
“…Numerous studies conrm that some BBR and/or their derivates contain biologically active substances (Fig. 3) which can induce signicant implications to biota, particularly affecting fungi and bacteria 119 as well as higher plants. 120 Alterations in bacterial communities and their compositions are mainly due 7 Response of soil pH reaction to fly bioash (A) and coal ash (B) application.…”
Section: Bio-based Resources (Bbr) and Implications To Biotamentioning
confidence: 99%